2018
DOI: 10.3390/cancers10090290
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study to Assess EGFR Mutational Status in Plasma: Focus on an Optimized Workflow for Liquid Biopsy in a Clinical Setting

Abstract: A multicenter study was performed to determine an optimal workflow for liquid biopsy in a clinical setting. In total, 549 plasma samples from 234 non-small cell lung cancer (NSCLC) patients were collected. Epidermal Growth Factor Receptor (EGFR) circulating cell-free tumor DNA (ctDNA) mutational analysis was performed using digital droplet PCR (ddPCR). The influence of (pre-) analytical variables on ctDNA analysis was investigated. Sensitivity of ctDNA analysis was influenced by an interplay between increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In a multicenter study, we observed a negative influence on plasma volume upon longer storage of blood samples in Streck tubes. Increased centrifugation speed was found to negate this effect [20,21], which is recommended by Streck. As plasma volume is directly associated with cfDNA concentration [22], it is doubtful whether protocols based on low centrifugation speed, such as the platelet-generating and (adapted) basic protocol, will generate sufficient material for the detection of low abundant aberrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multicenter study, we observed a negative influence on plasma volume upon longer storage of blood samples in Streck tubes. Increased centrifugation speed was found to negate this effect [20,21], which is recommended by Streck. As plasma volume is directly associated with cfDNA concentration [22], it is doubtful whether protocols based on low centrifugation speed, such as the platelet-generating and (adapted) basic protocol, will generate sufficient material for the detection of low abundant aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…cfDNA isolation was performed using the Maxwell RSC ccfDNA large volume plasma kit (Promega, Leiden, The Netherlands) according to the manufacturer’s protocol. Detailed procedures are described elsewhere [20]. Plasma samples were processed immediately after thawing, with the exception of the adapted basic protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Liquid biopsy, consisting of biomarker testing, for example, mutations in cell free DNA (cfDNA), has emerged as an important approach to guide therapeutic decisions. 9–13 A liquid biopsy is generally accompanied by simple blood collection and can enable real-time follow-up. Because of challenges associated with the availability of archived tissue, liquid biopsies are often performed to detect cancer-specific mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there are almost no data on how to handle these fluids in a way to optimize the isolation and characterization of extracellular nucleic acids. In a "seven at one blow" approach, Sorber and colleagues tried to analyze the effect of a variety of different pre-analytical factors on the sensitivity of a test for the detection of EGFR mutations in the plasma of lung cancer patients [88]. One of their conclusions reads that "A longer transit time was associated with a lower amount of plasma" in combination with a one-step low-speed centrifugation protocol for plasma processing.…”
Section: What Happens When Processing Of Blood or Biological Fluids Imentioning
confidence: 99%